Analisis pengaruh variabel makroekonomi terhadap pertumbuhan ekonomi di Indonesia tahun 2017-2022 - Kusuma, Devinna Putri Vania; Purnomo, Didit (Nur Science Institute, 2024)
This research aims to analyze the influence of macroeconomic variables on economic growth in Indonesia in 2017-2022. The data analysis method used in this research is a quantitative analysis method. The population of this research is data on Indonesia's economic growth for 2017–2022. The research sample taken was Indonesia's economic growth report for 2017–2022. The type of data in this research is secondary data. The data analysis technique used in this research measures economic growth with macroeconomic variables. The data analysis method used in this research is multiple linear regression. The research results show that government spending does not affect economic growth. Meanwhile, investment has a positive effect on economic growth. Apart from that, unemployment has a positive effect on economic growth.